THE ASSOCIATION BETWEEN BODY MASS INDEX (BMI) AND GASTROESOPHAGEAL REFLUX DISEASE (GERD) INCIDENCE AMONG VISITORS AT THE GASTROENTEROLOGY CLINIC OF RSUP DR. MOHAMMAD HOESIN PALEMBANG - Zuhdi, Kgs. Muhammad; Astoni, Muhamad Ayus; Rasyid, Riana Sari Puspita; Suprianto, Imam; Prasasty, Gita Dwi (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
This study aimed to determine the association between BMI and the incidence of GERD in visitors to the Gastroclinic of RSUP Dr. Mohammad Hoesin Palembang. A total of 153 samples met the eligibility requirements, this study used a random sampling technique and collected primary data through a questionnaire instrument. Data were analyzed using SPSS Statistic V27 in univariate, bivariate (chi-square test) and multivariate (logistic regression enter method) analysis. The majority of GERD patients were aged 36-65 years (46.7%), male sex (46.2%) and BMI in the obese category (65.9%). The results of this research showed no significant association among age and sex in the incidence of GERD, but there was a significant association between BMI on the incidence of GERD (p=0.003) thus being the most significant variable in this research (p=0.012). In conclusion, there is a significant association between BMI and the incidence of GERD while there is no significant association among age and sex in the incidence of GERD.